Increased gut microbiota diversity in women with uterine fibroids: Insights from a pilot study on gut and reproductive tract microbiota - Lidia Korczyńska; Michalina Dąbrowska; Maria Kulecka; Piotr Olcha; Tomasz Łoziński; Maciej Brązert; Jerzy Ostrowski; Ewa E. Hennig; Michał Ciebiera; Natalia Zeber-Lubecka (PLoS ONE, 2025)
Uterine fibroids (UFs) are still mysterious lesions, they are influenced by hormonal imbalances and chronic inflammation, with recent emerging evidence suggesting a role for microbiota. While gastrointestinal and vaginal microbiota in UF patients have been moderately explored, this study uniquely examines endometrial microbiota in women with UFs. Aim of this study was to investigate the microbiota composition in the uterine cavity, cervix and stool using 16S rRNA bacterial gene sequencing, alongside the concentration of bacterial metabolites in stool samples, comparing women with UFs to a control group. Results revealed no statistically significant differences in α- and β-diversity in cervical swab and endometrial tissue samples between patients with UFs and controls. However, detailed analyses highlighted the overrepresentation of Lactobacillus iners in cervical samples of patients with UFs, a species often associated with vaginal dysbiosis. Gut microbiota analysis demonstrated increased Shannon index measured α-diversity in patients with UFs, yet no differences in richness or β-diversity. While short-chain fatty acids (SCFAs) modulate inflammation and immunity, this study found no significant differences in SCFA or amino acid levels, though trends warrant further investigation. The small sample size and microbiota variability limited statistical significance, emphasizing the need for larger studies to unravel microbiota’s complex role in UF pathogenesis. In conclusion, the study underscores microbiota’s potential impact on gynecological health and highlights avenues for future research, including microbiome-targeted therapies for UFs and related disorders.